Rigosertib versus best supportive care for patients with high-risk myelodysplastic syndromes after failure of hypomethylating drugs (ONTIME): a randomised, controlled, phase 3 trial. Issue 4 (April 2016) - Garcia-Manero, Guillermo; Fenaux, Pierre; Al-Kali, Aref; Baer, Maria R; Sekeres, Mikkael A; Roboz, Gail J; Gaidano, Gianluca; Scott, Bart L; Greenberg, Peter; Platzbecker, Uwe; Steensma, David P; Kambhampati, Suman; et al.
Summary: Background: Hypomethylating drugs are the standard treatment for patients with high-risk myelodysplastic syndromes. Survival is poor after failure of these drugs; there is no approved second-line therapy. We compared the overall survival of patients receiving rigosertib and best supportive care with that of patients receiving best supportive care only in patients with myelodysplastic syndromes with excess blasts after failure of azacitidine or decitabine treatment. Methods: We did this randomised controlled trial at 74 hospitals and university medical centres in the USA and Europe. We enrolled patients with diagnosis of refractory anaemia with excess blasts (RAEB)-1, RAEB-2, RAEB-t, or chronic myelomonocytic leukaemia based on local site assessment, and treatment failure with a hypomethylating drug in the past 2 years. Patients were randomly assigned (2:1) to receive rigosertib 1800 mg per 24 h via 72-h continuous intravenous infusion administered every other week or best supportive care with or without low-dose cytarabine. Randomisation was stratified by pretreatment bone marrow blast percentage. Neither patients nor investigators were masked to treatment assignment. The primary outcome was overall survival in the intention-to-treat population. This study is registered with ClinicalTrials.gov, NCT01241500 . Findings: From Dec 13, 2010, to Aug 15, 2013, we enrolled 299 patients: 199 assigned to rigosertib, 100 assigned to best supportive care. Median follow-up was 19·5 months (IQR 11·9–27·3). As of Feb 1, 2014, median overall survival was 8·2 months (95% CI 6·1–10·1) in the rigosertib group and 5·9 months (4·1–9·3) in the best supportive care group (hazard ratio 0·87, 95% CI 0·67–1·14; p=0·33). The most common grade 3 or higher adverse events were anaemia (34 [18%] of 184 patients in the rigosertib group vs seven [8%] of 91 patients in the best supportive care group), thrombocytopenia (35 [19%] vs six [7%]), neutropenia (31 [17%] vs seven [8%]), febrile neutropenia (22 [12%] vs ten [11%]), and pneumonia (22 [12%] vs ten [11%]). 41 (22%) of 184 patients in the rigosertib group and 30 (33%) of 91 patients in the best supportive care group died due to adverse events and three deaths were attributed to rigosertib treatment. Interpretation: Rigosertib did not significantly improve overall survival compared with best supportive care. A randomised phase 3 trial of rigosertib (NCT 02562443 ) is underway in specific subgroups of patients deemed to be at high risk, including patients with very high risk per the Revised International Prognostic Scoring System criteria. Funding: Onconova Therapeutics, Leukemia & Lymphoma Society.